An H∞ LPV control for a class of LPV systems using a descriptor approach: Application to a wind turbine mode. Issue 26 (2015) - Ali, Harouna Souley; Darouach, Mohamed; Zasadzinski, Michel; Alma, Marouane
Abstract: This paper is devoted to the synthesis of an H∞ LPV state feedback controller, applied to a wind turbine which is described by an LPV model. Firstly, we focus on the modeling of wind turbines, to propose a model that describes as good as possible the system behaviour. A new approach that allows us, via LMIs, to design an LPV controller for a class of LPV systems is then presented. The interest of the approach is to decouple the system dynamic matrix and the lyapunov one using a desriptor approach. Finally, to illustrate the proposed control strategy, some simulation results are presented.